Análise da série histórica de malária residual em municípios do Espírito Santo com sistemas de Mata Atlântica no período de 2007 a 2018 - Mendonca, Gustavo Vital de (2019)
Introduction: Malaria, for thousands of years, has remained one of the most important infectious diseases occurring in humans. It is caused by protozoa of the genus Plasmodium, being transmitted by the bite of the infected female mosquito of the genus Anopheles. The autochthonous malaria of the Atlantic Forest, or residual malaria of the Atlantic Forest systems (RSMA), is due to the presence of the bromeliads, whose whorls are used in the reproduction of the Anopheles mosquitoes of the subgenus Kerteszia. These are considered the primary vectors of both human malaria and simian malaria in this region, which raises the question of whether bromeliad malaria could be considered a zoonosis. In the first half of 2017, Brazil experienced a large outbreak of yellow fever, and up to May 31, 2017, 3,850 deaths of non-human primates were reported to the Ministry of Health, 642 of which were confirmed for yellow fever by laboratory criterion or epidemiological link. Objectives: To evaluate the impact of the yellow fever epizootic on the cases of residual malaria in the Atlantic Forest systems and to evaluate the association of climatic factors with the occurrence of malaria in the study region. Methods: A database containing the cases of autochthonous malaria recorded in the municipalities of Domingos Martins and Santa Teresa (n = 244), in the mountain region of the state of Espírito Santo, between 2007 and 2018 was developed. Analysis were performed using a Poisson regression model with the adoption of a three-month moving average. Results: The Poisson models were able to demonstrate a negative correlation between the yellow fever epizootic and the number of malaria cases. A statistically significant positive correlation was found between the number of malaria cases and the mean maximum temperature in the previous month. The adopted model presented low power of explanation given the multifactorial nature of the transmission chain. We conclude that apes play an important role in the occurrence of Atlantic Forest malaria, but their presence is not enough to explain all the aspects of the complex chain of transmission. Keywords: malaria, epidemiology, bromeliad, Poisson distribution, yellow fever.